Sensory and physical perceptions of the Roman round-up of 16-18 October 1943 in Elsa Morante’s La Storia: a cultural memory perspective - Mara Josi (Laboratoire Italien)
This article looks at the literary re-elaboration of the round-up occurred in Rome between 16 and 18 October 1943 in La Storia by Elsa Morante. It considers Morante’s Jewish origins and impegno in writing of World War II and re-reads her description of this event in the light of cultural memories studies. It summarises key events of her life, as they related to World War II and to the German occupation of Rome, and examines her commitment to interrogate the past through literature. Literature is, indeed, a bearer of historical knowledge and a medium of memory; literary texts are not only an outcome of remembrance, but also an active ingredient in the ongoing process of cultural memory. Morante’s literary representation of the events of 16 and 18 October 1943 is also read through the lens of her depiction of the sensory perceptions of the main characters, Ida e Useppe. This analysis shows how and to what extent the author fosters what Alison Landsberg calls “prosthetic memory”.